Vitamin levels in Behcet's disease - Kandi, Basak; Cicek, Demet; Ilhan, Nevin (Taylor & Francis Ltd, 2007)
Objective: To determine the role of oxidative stress and the antioxidant defense mechanism in the etiopathogenesis of active and inactive Behcets disease. In line with this objective, the present study aimed to examine the levels of nitric oxide (NO) and malondialdehyde (MDA), which are the end products of oxidant stress, and vitamins, which are non-enzymatic antioxidants, for the diagnosis and particularly the follow-up of Behcet's disease. Materials and methods: The study group consisted of a total of 60 individuals: 40 of whom were Behcet's disease patients and 20 were healthy individuals. Of the 40 Behcet's patients, 29 had the active and 11 had the inactive (stable) form of the disease. Results: Although plasma MDA and NO (its stable form nitrite) levels in the total patient group were statistically significantly higher than those in the control group (p < 0.06), there was no statistically significant difference as such between inactive Behcet's patients and the control group (p > 0.05). Vitamin E, C, B1, B2 and flavin mononucleotide (FMN) values were significantly lower in the patient group in comparison with the control group (p < 0.05). There was no statistically significant difference in other vitamin values. Discussion: It is contemplated that measurement of such oxidative stress factors as MDA and NO and an accompanying evaluation of the antioxidant defense system can be significant in the diagnosis and treatment follow-up of Behcet's disease.
Keywords: Behcet's disease; MDA; NO; vitamins